EFFECTS OF ADVERSE EVENTS ON THE HEALTH RELATED QUALITY OF LIFE OF COPD PATIENTS, A CROSS SECTIONAL STUDY IN TERTIARY CARE HOSPITALS OF LAHORE, PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Objectives: Whether chronic obstructive pulmonary disease (COPD) standard treatment adverse effects had any impact on health related quality of life of COPD patients?Method: A cross-sectional observational study conducted in six different tertiary care hospitals in Lahore over two months, from April to June 2025. The study included 385 indoor and outdoor patients with the age of 30 years and above either male or female, irrespective of their co-morbid conditions i.e., CVD, emphysema, asthma, hypertension. Patients with CKD, blood dyscrasias, immuno-compromised were excluded from this study. Data were collected through direct interview from the indoor and outdoor patients during their hospital visits by using structured and validated questionnaires. By using IMB SPSS Software descriptive statistics, chi-Square test and linear regression test were employed to analyze the collected data.Result: This study showed that age (p = 0.001), smoking status (p = 0.001), COPD duration (p = 0.001) and treatment (p = 0.001) were associated with the severity of COPD. Similarly, the most common adverse effect of COPD medication was dry mouth (p = 0.001) occuring in 73.8% patients but had no significant correlation with daily functional areas. Muscle cramps was occurred in 52.5% of patients and had statistically significant correlations with mobility (p = 0.01), self-care (p = 0.004), pain (p = 0.002) and anxiety (p = 0.033). Tachycardia (30.6%) was most related to self-care (p = 0.017) and palpitations (15.3%) affected usual activities (p = 0.015). Urinary retention (12.5%) was related to higher anxiety (p = 0.012). Swelling (18.2%) and constipation (40.3%) had no significant impact on any of the health quality dimensions. The results of linear regression test showed that, three adverse effects urinary retention (p = 0.015), tachycardia (p = 0.018) and muscle cramps (p = 0.025) were associated with the standard treatment of COPD.Conclusion: This study concludes that age, smoking and duration of COPD were associated with the severity of COPD. The most common adverse effect associated with COPD standard treatment such as: muscle cramp, tachycardia, palpitation and urinary retention had significant impact on patient’s quality of life.